Impact of sustainability mediated by corporate governance in extra large size microfinance institutions of Bangladesh - Uddin, Md Nazim; Haque, A K M Ahasanul; Nuruzzaman, Md.; Nahar, Lutfun (Springer, 2024)
This experimental study investigates the correlation between profitability and corporate governance in Bangladeshi MFIs. The study focuses on Bangladesh Microcredit Regulatory Authority (MRA)—classified extra-large MFIs. The research emphasizes the importance of corporate governance (CG) for these enterprises and discusses governance challenges in Bangladesh. STATA-17 is used to do the analysis. MRA, Grameen Bank, and MIX data are evaluated using panel data analysis and regression. The top five Bangladeshi MFIs were surveyed between 2012 and 2021. The results show that board size, competence, and diversity impact institutional survival. The relationship between board competence and sustainability did not hold for board size. Diversity is detrimental to sustainability, although women on boards are beneficial. The findings support the notion that strong corporate governance measures, including board competence, diversity, and female board members, enhance the sustainability of MFIs in Bangladesh.